2007
DOI: 10.1139/g07-056
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a genetic linkage map forSaccharum officinarumincorporating both simplex and duplex markers to increase genome coverage

Abstract: Saccharum officinarum L. is an octoploid with 80 chromosomes and a basic chromosome number of x = 10. It has high stem sucrose and contributes 80% of the chromosomes to the interspecific sugarcane cultivars that are grown commercially for sucrose. A genetic linkage map was developed for S. officinarum (clone IJ76-514) using a segregating population generated from a cross between Q165 (a commercial sugarcane cultivar) and IJ76-514. In total, 40 AFLP and 72 SSR primer pairs were screened across the population, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
5

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 22 publications
0
52
0
5
Order By: Relevance
“…A very low level of single-dose markers (Wu et al 1992), the only type of markers easily used for mapping in sugarcane, was obtained for the female parent IJ76-514. This signiWcantly hampered construction of the IJ76-514 genetic map and was interpreted as a low level of heterozygosity in this S. oYcinarum clone (Aitken et al 2007). Our results clearly revealed that 2n transmission has occurred in this population; the implications of this should also be considered in the analysis of mapping data.…”
Section: N + N Chromosome Transmissionmentioning
confidence: 99%
“…A very low level of single-dose markers (Wu et al 1992), the only type of markers easily used for mapping in sugarcane, was obtained for the female parent IJ76-514. This signiWcantly hampered construction of the IJ76-514 genetic map and was interpreted as a low level of heterozygosity in this S. oYcinarum clone (Aitken et al 2007). Our results clearly revealed that 2n transmission has occurred in this population; the implications of this should also be considered in the analysis of mapping data.…”
Section: N + N Chromosome Transmissionmentioning
confidence: 99%
“…Comparable number of LG and map length were found in the female (S. officinarum ' La Striped'; 49 LG with 1732 cM) and male (S. spontaneum 'SES 147B';45 LG with 1491 cM) maps in our study. Recently Aitken et al (2007) constructed a linkage map of S. officinarum with 123 LG spanning 4306 cM with 534 linked SD, DD, TD and QD markers. To our knowledge, this is the first attempt to use AFLP in combination with either SRAP and/or TRAP markers for constructing linkage maps in these progenitor species of sugarcane.…”
Section: Map Constructionmentioning
confidence: 99%
“…Recently, Edmé et al (2006) developed a S. spontaneum and S. officinarum map using SSR markers. AFLP markers have so far been used to construct genetic linkage maps of commercial sugarcane (Hoarau et al 2001;Aitken et al 2005;Reffay et al 2005) and recently of S. officinarum (Aitken et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Two linkage maps were constructed from this F 1 segregating population with 344 polymorphic markers from the female parent La Striped and 306 markers from the male parent SES 147B, yielding 49 and 45 linkage groups, respectively (Aitken et al 2007). …”
Section: Genetic Mappingmentioning
confidence: 99%